Pengaruh Strategi Pemasaran dan Citra Perusahaan Terhadap Keputusan Nasabah Untuk Menabung di KSPPS BMT Kemitraan Bojonegoro - Habib, Zainal; Mundhori (Sharia Business Management Study Program, Faculty of Economics and Islamic Business at IAIN Kediri, 2021)
The decision to save is one of the problems experienced by every financial institution, both conventional and sharia-based, where the customer's decision is influenced by several factors, including marketing strategy factors and corporate image. This is interesting because the marketing strategy and corporate image are factors that have a significant level of risk. The purpose of this study was to determine the effect of marketing strategy and corporate image on customer decisions to save at KSPPS BMT Kemitraan Bojonegoro. The method used in this study is quantitative, data collection methods used are questionnaires, documentation, and observation. The analytical method used in this research is multiple regression analysis. The results show that partially, marketing strategy has a positive and significant effect on customer decisions to save and company image has a positive and significant effect on customer decisions to save. Meanwhile, simultaneously marketing strategy and corporate image have a positive and significant effect on customer decisions to save. The magnitude of the influence of marketing strategy and corporate image is 47.3% which is indicated by the value of the determinant coefficient and the rest is influenced by other variables.